Planning an agent-based network for livestock production and meat distribution in Mongolia - Yan, Wanglin, author; Oba, Aikihiro, author; Balt, Suvdantsetseg, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
This paper reviews the problems of livestock production in Mongolia and proposes an agent-based meat distribution network composed of multiple players. Agents sell and buy products and services, equipped with intelligent capacity of knowledge and physical capacity of freezing meat stock, livestock, and forage stock. Local governments and communities are the key for enhancing food security. The network, as a whole, is green, clean and resilient to climatic and market disturbance.
Planning a multi-agent network for livestock production and meat distribution in Mongolia
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: food security; agent-based network; local development; meat freezing storage